PERTUMBUHAN DAN PRODUKSI BERBAGAI VARIETAS TANAMAN KEDELAI DI LAHAN SAWAH TADAH HUJAN - -, St. Subaedah; Ralle, Andi; -, Netty (Jurnal Ilmiah Ecosystem, 2019)
This study aims to look for soybean varieties that provide high production in rainfed lowland rice fields. This research was conducted in the form of an experiment in Takalar district, South Sulawesi. The experiment was designed with a Randomized Block Design, which consisted of five treatments, namely: Anjasmoro Varieties; Agromulyo; Kaba; Tidar and Gepak Kuning. Each treatment was repeated three times. The results showed that different varieties significantly affected soybean crop production, where Anjasmoro and Agromulyo varieties produce the highest number of pods, pod weights and soybean seeds production, while the Gepak Kuning variety produces the lowest number of pods and pod weights and seed production